Strategi inovasi pengembangan kompetensi dosen menuju sumber daya manusia unggul pada pasca pandemi Covid-19 di Universitas Jambi - Hendriyaldi, Hendriyaldi; Sumarni, Sumarni (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2023)
One of the keys to the success of higher education is the quality of human resources or lecturers. This research aims to determine the implementation of innovative strategies for developing lecturer competencies towards superior human resources in the post-covid-19 pandemic at Universitas Jambi. This research uses descriptive qualitative research. Data collection techniques used in research include observation, interviews, documentation and literature study using steps including data reduction, data presentation and drawing conclusions. Triangulation in this qualitative research uses source triangulation, namely the researcher will make comparisons and check information obtained through different times and tools. The conclusion of this research is that the strategy for developing lecturer competencies begins with mapping lecturer competencies, developing curriculum and learning methods, developing training programs, developing lecturers and evaluating assessments. The development of lecturer competencies towards superior human resources needs to be improved, including digital competency development, pedagogical competency development, research competency development, professional competency development, and leadership competency development for lecturers.